Dari Tragedi Lokurata hingga Involusi Pertanian: Amatan Seorang Antropolog tentang Perubahan Lingkungan dan Pola-pola Tindakan Manusia di Desa Ngadu Olu - Sahrul Aksa . (Universitas Khairun, 2016)
The article is based participatory observation at Ngadu Olu, Central Sumba,East Nusa Tenggara. Observations were made with track themes related toIntegrated Agriculture, Renewable Energy, and Green Entrepreneurship,Emerging Being latter Structuring Issues Region. Research assumption is thatthe ecological crisis impact in decrease the environmental carrying capacity ofproduction economic activities in the village. This article discusses that thesubsistence and involution can happened on the ground that still rich. Thatcircumstances can occurs when the factors of production in the village notcome support the innovation leap farming as terms exit from rontgentsubsistence. Transformation from farmers to have farmers terms should worktogether.